2021
DOI: 10.3389/fnins.2021.633988
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Temporal Interference for Non-invasive Deep Brain Stimulation in Epilepsy

Abstract: In patients with focal drug-resistant epilepsy, electrical stimulation from intracranial electrodes is frequently used for the localization of seizure onset zones and related pathological networks. The ability of electrically stimulated tissue to generate beta and gamma range oscillations, called rapid-discharges, is a frequent indication of an epileptogenic zone. However, a limit of intracranial stimulation is the fixed physical location and number of implanted electrodes, leaving numerous clinically and func… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 40 publications
1
51
0
Order By: Relevance
“…For example, Grossman et al (2017) used c-Fos immunochemistry to demonstrate activation of the hippocampus without activating superficial cortical areas, with strong c-Fos immunoreactivity in the entire region of granule cells within the dentate gyrus. This expression was much stronger than observed anywhere for LFS or elsewhere in TIS, suggesting that TIS achieved strong synchronous activation of the local circuitry in the dentate gyrus, consistent with a seizure-like event evoked by TIS in awake rat (Missey et al, 2021). Furthermore, the area of activation indirectly inferred based on immunohistochemistry does not correlate with the distribution of the simulated E-field modulation envelope amplitude (Grossman et al, 2017, fig.…”
Section: Discussionsupporting
confidence: 55%
“…For example, Grossman et al (2017) used c-Fos immunochemistry to demonstrate activation of the hippocampus without activating superficial cortical areas, with strong c-Fos immunoreactivity in the entire region of granule cells within the dentate gyrus. This expression was much stronger than observed anywhere for LFS or elsewhere in TIS, suggesting that TIS achieved strong synchronous activation of the local circuitry in the dentate gyrus, consistent with a seizure-like event evoked by TIS in awake rat (Missey et al, 2021). Furthermore, the area of activation indirectly inferred based on immunohistochemistry does not correlate with the distribution of the simulated E-field modulation envelope amplitude (Grossman et al, 2017, fig.…”
Section: Discussionsupporting
confidence: 55%
“…In a previous study, we showed that it was possible to evoke seizures like events with PMW-TI (45) , the same wave was used here to perform the current study. To analyze the non-invasive DBS like effect of stimulation with TI at 130Hz (TI HFS), we compared its impact with a cortical, TCS-like, high frequency stimulation (CT HFS) and a non-treatment group (Sham) on hippocampal electrophysiological biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…This heavily influences the electric field lines. With this method, the importance of the direction of the electric field can be shown [26].…”
Section: Discussionmentioning
confidence: 99%
“…This heavily influences the electric field lines. With this method, the importance of the direction of the electric field can be shown [26]. In the study of the underlying mechanism, it can be considered to investigate more morphologically correct neurons to include propagation of the signal through a neuron.…”
Section: Limitations and Future Workmentioning
confidence: 99%